Identidade(s) latino-americana(s) no ensino de História: um estudo em escolas de ensino médio de Belo Horizonte, MG, Brasil - Alves, Thamar Kalil de Campos (2011)
This investigation has had as research object the Latin American identities in History teaching, in high schools at Belo Horizonte, Minas Gerais, Brazil, in the first decade of the 21st century. The guiding issues were: How is History teaching in Latin America established in the official curricula and didactic production? Is there any evidence of the the Latin American identity in the process of teaching developed in the medium level schools at Belo Horizonte in the first decade of this century? The research aims at analyzing how Latin American identity is set up in the historical knowledge conveyed and disseminated by textbooks, official programs for teaching history and in readings, as well as the concepts (re)produced by students and teachers, in the context of teaching history in high school. The specific objectives were: a) to analyze the history of Latin America in the official curricula for the teaching of history; b) identify and describe the places and subjects of the investigation process in the context of high school; c) analyze knowledge and pedagogical practices related to teaching Latin American History in high school; and d) reflect on the evidence(s) of Latin American identity (ies) students in the student s narratives of history teachers in high school. It is a qualitative survey with thematic oral interviews which were transcribed and textualized with bibliographical, documental and iconographic research. The subjects investigated were teachers and students of history of the third year of high school in 02 elementary public schools, and one private school at Belo Horizonte, Minas Gerais, Brazil, in 2009. The thesis is organized into four chapters: The first chapter presents the history of Latin America in the official curricula for the teaching of history in Brazil, from the late nineteenth century to the beginning of the twentieth century. The second chapter describes and analyzes the locations and subjects of the research. The third chapter deals with the didactic production, books, curricula and teaching plans, knowledge and pedagogical practices. The fourth chapter presents a discussion on indications of the Latin American identity in the narratives of students and teachers investigated. The study reveals how the historicity of education programs and curricula (re)produce particular identities in different contexts. It was observed that places, subjects and identities keep singularities in the midst of the collective ambient in the dynamics of a globalizing society. It was evident that the teachers investigated do not know and even silence the interests of students, the place, and role of learning about Latin America thematic in youth formation. The school teaching and the student s learning on the subject have proved to be as different movements that are different and even divergent in the educational practice. The research evidenced the students interest in the subject, with the need to listen to them for the reorientation of educational practices and reconfiguration of knowledge and identity(ies).